Comparison of Vaginal Culture and Pap smear in the Diagnosis of Bacterial Vaginosis - Iqbal, Mehreen; Sultana, Nuzhat; Durrani, Saadia Haroon; Zubair, Muhammad; Tariq, Shazia (International Journal of Pathology, 2018)
Background: Amongst the myriad of physiological and pathological conditions presenting as vaginal discharge, bacterial vaginosis is the most frequently encountered complaint in women of child bearing age, all over the world. It involves the replacement of normally predominant hydrogen-peroxide producing lactobacilli, by an overgrowth of anaerobic bacteria. We want to examine the diagnostic efficacy of Pap-Smear and vaginal culture in the diagnosis of bacterial vaginosis, while Amsel’s clinical criteria is used as the gold standardMethods: It was a descriptive study expanding over a period of 5 months, from January 2013 to May 2013, enrolling 150 patients, from the outpatient’s department of lady reading hospital and Hayatabad medical complex, Peshawar. All patients who complained of vaginal discharge were eligible for study. Patients using antibiotics, vaginal suppositories as well as those who were pregnant were excluded from the study. All patients were subjected to simultaneous testing for Amsel’s criteria, vaginal culture, and Pap-staining. Sensitivity, specificity, positive predictive value and negative predictive values were calculated for vaginal culture and Pap smear, with amsel’s criteria being the gold standard.Results: Sensitivity, specificity, positive and negative predictive values for culture was determined as 75%, 92.1%, 64.3% and 95.1%. Pap smear was found to be 62.5% sensitive, 93.7% specific, positive and negative predictive values being 65.2% and 92.9% respectively.Conclusion: Out of these two tests, vaginal culture was labeled as the more sensitive test for the diagnosis of bacterial vaginosis.